Effect of Hypoglycemic Drugs on Kisspeptin Expression in the Hypothalamic Arcuate Nucleus of PCOS Rats - Zheng P; Lu Y; Tang Y; Xu F; Wang L; Qian R; Hui C; Xu Q; He J; Deng D (Diabetes, Metabolic Syndrome and Obesity, 2023)
Pingping Zheng,1,* Yating Lu,2,* You Tang,1,* Fudong Xu,3 Lin Wang,2 Rui Qian,4 Cancan Hui,5 Qian Xu,2 Jianle He,1 Datong Deng2 1The General Practice Department, the First Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei, People’s Republic of China; 2The Endocrinology Department, the First Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei, People’s Republic of China; 3The Pathology Department, Beijing Chest Hospital, Capital Medical University, Beijing Tuberculosis & Thoracic Tumor Research Institute, Shoudu Medical University, Beijing, People’s Republic of China; 4The Neurology Department, the First Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei, People’s Republic of China; 5The Geriatric endocrinology Department, the First Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Datong Deng, Tel +86 13855134251, Fax +86 055163633742, Email 13855134251@163.comBackground: To investigate the change in hypothalamic kisspeptin-1 (Kiss1) expression during the development of polycystic ovary syndrome (PCOS) and hypoglycemic drug intervention.Methods: Letrozole lavage was used to construct a polycystic ovary rat model. After successful modeling, we treated PCOS rats with metformin, pioglitazone, and acarbose, and we then observed changes in weight, estrus, glucose tolerance, insulin resistance, sex hormones, and hypothalamic kiss1 expression.Results: PCOS rats exhibited increased body weight, abnormal estrous cycle, impaired glucose tolerance, insulin resistance, increased testosterone level, increased luteinizing hormone level, and increased Kiss1 expression in the hypothalamus. However, intervention with metformin, pioglitazone, and acarbose improved the reproductive and metabolic disorders as well as reduced hypothalamic Kiss1 expression.Conclusion: The expression of hypothalamic Kiss1 may play an important role in the pathogenesis of PCOS. Metformin, pioglitazone, and acarbose may reduce the expression of hypothalamic Kiss1 by improving insulin resistance, thereby improving reproductive and metabolic disorders in PCOS rats.Keywords: polycystic ovary syndrome, PCOS, kisspeptin, metformin, pioglitazone, acarbose